(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Male infertility is most obvious examples of a complex disease. Genetic factors of spermatogenic dysfunction, like as chromosomal aberrations, account for 10–15 percent of extreme male infertility, according to many male mouse models, mutation screening, and correlation studies conducted in the last few years. The standard GTG (G-banding Trypsin Giemsa) banding technique was used to determine the chromosomal abnormalities. A total of 68 percent of study participants had azoospermia, 18 percent had oligospermia, 6 percent had severe oligospermia, and 8 percent had oligoasthenoteratospermia (OAT) xvi.